A widely applicable plasma renin activity assay by LC-MS/MS with offline solid phase extraction. (May 2014) - Owen, Laura J; Adaway, Joanne; Morris, Karen; Lockhart, Stephen; Keevil, Brian G
Background: The measurement of plasma renin activity using LC-MS/MS is an attractive alternative to radioimmunoassay techniques. A published method for renin activity by LC-MS/MS uses equipment that is not available in all LC-MS/MS laboratories. Here, we present an offline modification to allow users of LC-MS/MS to perform this analysis without specialist equipment. Methods: Samples were prepared in duplicate and incubated for 6.5 h and 24 h. Solid phase extraction was performed offline using Waters Oasis MAX ion-exchange 96-well plate. A method comparison was performed between this assay and a previously published assay using on-line solid phase extraction. Results: The offline method for plasma rennin activity gave similar results to the on-line method across the concentration range. Analytical performance was also found to be comparable and the use of a 24 h incubation for low samples was also deemed unnecessary. Discussion: The method described is an acceptable alternative to a previously published assay which does not require the use of highly specialist equipment and will be applicable to the majority of LC-MS/MS users.